Linking Language Learning, Technology, and Sustainability through Project-Based Ecotourism Education - Desi Wijayanti Ma'rufah; Yulian Purnama; Rafi Akmal Saputra; Ana Mae M. Monteza; Pipit Muliyah (Universitas Islam Negeri Madura, 2026)
This study explores how Technology Project-Based Learning (TPBL) can be integrated into the English for Tourism curriculum at UIN Saizu Purwokerto to create media-based products promoting sustainable ecotourism in Banyumas, Central Java. Banyumas has a lot of natural and cultural resources that could be used for ecotourism, but the local marketing strategies do not always use new and educational media. The study used a Research and Development (R&D) approach with both qualitative and quantitative methods. The participants of this study are English for Tourism students and tourism stakeholders. The data are collected through observation, interviews, and focus group discussions. By implementing TPBL, students produce digital media: videos, social media campaigns, and websites for introducing local tourism objects in Banyumas. The results show that using TPBL enchances students' creativity, critical thinking, teamwork, and environmental awareness, and it also produces authentic practice that promote sustainable tourism. The study finds that TPBL not only helps students learn a new language, but it also changes the way teachers teach by integrating education, technology, and local sustainability.